Psychological Status Observation Among the Medical Students using DASS21 (Bangladesh Journal of Medical Science, 2024)
Background The psychological disorders like depression, anxiety, and stress seem significantly more prevalent in medical students than in general people nowadays. The medical courses with tedious academic activities raise this mental distress among them. In addition, demographic and biological factors have a citable impact on mental illness. Thus, to analyze these health issues, many studies have been done based on the DASS- Depression Anxiety Stress Scale, where DASS21 comprises 21 questionnaires. Objectives To highlight the correlation between demographic features and DASS21 attributes. Determining the severity of depression, anxiety, and stress in medical students, and observing the percentage-wise relation between preferred features – BMI, Blood Pressure, and Blood Group – and DASS21 attributes. Methods An online survey was conducted on Uttara Adhunik Medical College undergraduate students in November 2023. Students’ demographic data, biological factors information, and responses from DASS21 questionnaires were taken in this survey. Further analysis of results and visual observation has been done through online and offline spreadsheets. Result Following the correlation coefficient test, students’ age and blood pressure negatively relate to DASS attributes; however, BMI is correlated positively with depression, anxiety, and stress. The severe prevalence rate of depression- 59%, anxiety- 72%, and stress- 53%, where females are more affected. The students who belong to the O and B blood groups as well as the overweight and obese students are more affected although most of them are healthier; nevertheless, depressed, anxious, and stressed students are mostly normotensive. Conclusion The present study highlights that most of the undergraduate medical students of UAMC, especially females are suffering from depression, anxiety, and stress issues. These psychological disorders are highly associated with their BMI, Blood Pressure, and Blood Groups.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1149-1158